In the Land of Peuceti: The Settlement of Jazzo Fornasiello (Gravina in Puglia - Bari) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
The excavation carried out by the University of Milan (2009-2013) allowed us to have more information about the peucetian settlement of Jazzo Fornasiello. The acquired data allowed us to define more precisely the life phases of the site, dated between the 6th and the end 4th century BC. The research conducted so far suggests to define the site of Jazzo Fornasiello as a rich agricultural settlement with many Greek influences.
Keywords: Peucezia; Dolii; settlement; fortification wall; burials